Strategic Issues Facing Transportation, Volume 2: Climate Change, Extreme Weather Events, and the Highway System: Practitioner’s Guide and Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 750: Strategic Issues Facing Transportation, Volume 2: Climate Change, Extreme Weather Events, and the Highway System: Practitioner’s Guide and Research Report provides guidance on adaptation strategies to the likely impacts of climate change through 2050 in the planning, design, construction, operation, and maintenance of infrastructure assets in the United States (and through 2100 for sea-level rise).In addition to the practitioner’s guide and research report, this project also developed the following items:• A software tool that runs in common web browsers and provides specific, region-based information on incorporating climate change adaptation into the planning and design of bridges, culverts, stormwater infrastructure, slopes, walls, and pavements.• Tables that provide the same information as the previously mentioned software tool, but in a spreadsheet format that can be printed.• Two spreadsheets that illustrate examples of the benefit-cost analysis of adaptation strategies discussed in Appendix B of Part I of NCHRP Report 750, Volume 2.These three items are available on a CD-ROM that is included with a print version of the report. The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.• Help on Burning an .ISO CD-ROM Image.• Download the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)NCHRP Report 750, Volume 2 is the second in a series of reports being produced by NCHRP Project 20-83: Long-Range Strategic Issues Facing the Transportation Industry. Major trends affecting the future of the United States and the world will dramatically reshape transportation priorities and needs. The American Association of State Highway and Transportation Officials (AASHTO) established the NCHRP Project 20-83 research series to examine global and domestic long-range strategic issues and their implications for state departments of transportation (DOTs); AASHTO's aim for the research series is to help prepare the DOTs for the challenges and benefits created by these trends.Other volumes in this series currently available include:• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 1: Scenario Planning for Freight Transportation Infrastructure Investment• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 3: Expediting Future Technologies for Enhancing Transportation System Performance• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 4: Sustainability as an Organizing Principle for Transportation Agencies• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 5: Preparing State Transportation Agencies for an Uncertain Energy Future• NCHRP Report 750: Strategic Issues Facing Transportation, Volume 6: The Effects of Socio-Demographics on Future Travel DemandCD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Preparing for the Future of Disaster Health Volunteerism: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On April 26, 2017, the Forum on Medical and Public Health Preparedness for Disasters and Emergencies convened a workshop during a 4-hour session of the 2017 Preparedness Summit. Participants discussed potential characteristics of society in the year 2042 and the key resources, tools, and opportunities necessary to support the development of a robust, scalable, and regularly engaged disaster health volunteer workforce prepared for such a future. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Increasing National Resilience to Hazards and Disasters: The Perspective from the Gulf Coast of Louisiana and Mississippi: Summary of a Workshop - Steve Olson (The National Academies Press, 2011)
Natural disasters are having an increasing effect on the lives of people in the United States and throughout the world. Every decade, property damage caused by natural disasters and hazards doubles or triples in the United States. More than half of the U.S. population lives within 50 miles of a coast, and all Americans are at risk from such hazards as fires, earthquakes, floods, and wind. The year 2010 saw 950 natural catastrophes around the world—the second highest annual total ever—with overall losses estimated at $130 billion. The increasing impact of natural disasters and hazards points to increasing importance of resilience, the ability to prepare and plan for, absorb, recover from, or more successfully adapt to actual or potential adverse events, at the individual , local, state, national, and global levels. Assessing National Resilience to Hazards and Disasters reviews the effects of Hurricane Katrina and other natural and human-induced disasters on the Gulf Coast of Louisiana and Mississippi and to learn more about the resilience of those areas to future disasters. Topics explored in the workshop range from insurance, building codes, and critical infrastructure to private-sector issues, public health, nongovernmental organizations and governance. This workshop summary provides a rich foundation of information to help increase the nation's resilience through actionable recommendations and guidance on the best approaches to reduce adverse impacts from hazards and disasters.
Keywords: Earth Sciences

Healthy, Resilient, and Sustainable Communities After Disasters: Strategies, Opportunities, and Planning for Recovery - Institute of Medicine (The National Academies Press, 2015)
In the devastation that follows a major disaster, there is a need for multiple sectors to unite and devote new resources to support the rebuilding of infrastructure, the provision of health and social services, the restoration of care delivery systems, and other critical recovery needs. In some cases, billions of dollars from public, private and charitable sources are invested to help communities recover. National rhetoric often characterizes these efforts as a "return to normal." But for many American communities, pre-disaster conditions are far from optimal. Large segments of the U.S. population suffer from preventable health problems, experience inequitable access to services, and rely on overburdened health systems. A return to pre-event conditions in such cases may be short-sighted given the high costs - both economic and social - of poor health. Instead, it is important to understand that the disaster recovery process offers a series of unique and valuable opportunities to improve on the status quo. Capitalizing on these opportunities can advance the long-term health, resilience, and sustainability of communities - thereby better preparing them for future challenges. Healthy, Resilient, and Sustainable Communities After Disasters identifies and recommends recovery practices and novel programs most likely to impact overall community public health and contribute to resiliency for future incidents. This book makes the case that disaster recovery should be guided by a healthy community vision, where health considerations are integrated into all aspects of recovery planning before and after a disaster, and funding streams are leveraged in a coordinated manner and applied to health improvement priorities in order to meet human recovery needs and create healthy built and natural environments. The conceptual framework presented in Healthy, Resilient, and Sustainable Communities After Disasters lays the groundwork to achieve this goal and provides operational guidance for multiple sectors involved in community planning and disaster recovery. Healthy, Resilient, and Sustainable Communities After Disasters calls for actions at multiple levels to facilitate recovery strategies that optimize community health. With a shared healthy community vision, strategic planning that prioritizes health, and coordinated implementation, disaster recovery can result in a communities that are healthier, more livable places for current and future generations to grow and thrive - communities that are better prepared for future adversities.
Keywords: Health and Medicine; Conflict and Security Issues

Implications of the California Wildfires for Health, Communities, and Preparedness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
California and other wildfire-prone western states have experienced a substantial increase in the number and intensity of wildfires in recent years. Wildlands and climate experts expect these trends to continue and quite likely to worsen in coming years. Wildfires and other disasters can be particularly devastating for vulnerable communities. Members of these communities tend to experience worse health outcomes from disasters, have fewer resources for responding and rebuilding, and receive less assistance from state, local, and federal agencies. Because burning wood releases particulate matter and other toxicants, the health effects of wildfires extend well beyond burns. In addition, deposition of toxicants in soil and water can result in chronic as well as acute exposures. On June 4-5, 2019, four different entities within the National Academies of Sciences, Engineering, and Medicine held a workshop titled Implications of the California Wildfires for Health, Communities, and Preparedness at the Betty Irene Moore School of Nursing at the University of California, Davis. The workshop explored the population health, environmental health, emergency preparedness, and health equity consequences of increasingly strong and numerous wildfires, particularly in California. This publication is a summary of the presentations and discussion of the workshop.
Keywords: Health and Medicine

Crisis Standards of Care: A Toolkit for Indicators and Triggers - Institute of Medicine (The National Academies Press, 2013)
Disasters and public health emergencies can stress health care systems to the breaking point and disrupt delivery of vital medical services. During such crises, hospitals and long-term care facilities may be without power; trained staff, ambulances, medical supplies and beds could be in short supply; and alternate care facilities may need to be used. Planning for these situations is necessary to provide the best possible health care during a crisis and, if needed, equitably allocate scarce resources. Crisis Standards of Care: A Toolkit for Indicators and Triggers examines indicators and triggers that guide the implementation of crisis standards of care and provides a discussion toolkit to help stakeholders establish indicators and triggers for their own communities. Together, indicators and triggers help guide operational decision making about providing care during public health and medical emergencies and disasters. Indicators and triggers represent the information and actions taken at specific thresholds that guide incident recognition, response, and recovery. This report discusses indicators and triggers for both a slow onset scenario, such as pandemic influenza, and a no-notice scenario, such as an earthquake. Crisis Standards of Care features discussion toolkits customized to help various stakeholders develop indicators and triggers for their own organizations, agencies, and jurisdictions. The toolkit contains scenarios, key questions, and examples of indicators, triggers, and tactics to help promote discussion. In addition to common elements designed to facilitate integrated planning, the toolkit contains chapters specifically customized for emergency management, public health, emergency medical services, hospital and acute care, and out-of-hospital care.
Keywords: Health and Medicine

Public Response to Alerts and Warnings Using Social Media: Report of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2013)
Following an earlier NRC workshop on public response to alerts and warnings delivered to mobile devices, a related workshop was held on February 28 and 29, 2012 to look at the role of social media in disaster response. This was one of the first workshops convened to look systematically at the use of social media for alerts and warnings—an event that brought together social science researchers, technologists, emergency management professionals, and other experts on how the public and emergency managers use social media in disasters.In addition to exploring how officials monitor social media, as well as the resulting privacy considerations, the workshop focused on such topics as: what is known about how the public responds to alerts and warnings; the implications of what is known about such public responses for the use of social media to provide alerts and warnings to the public; and approaches to enhancing the situational awareness of emergency managers. Public Response to Alerts and Warnings Using Social Media: Report of a Workshop on Current Knowledge and Research Gaps summarizes presentations made by invited speakers, other remarks by workshop participants, and discussions during parallel breakout sessions. It also points to potential topics for future research, as well as possible areas for future research investment, and it describes some of the challenges facing disaster managers who are seeking to incorporate social media into regular practice.
Keywords: Conflict and Security Issues; Computers and Information Technology

Tools and Methods for Estimating Populations at Risk from Natural Disasters and Complex Humanitarian Crises - National Research Council (The National Academies Press, 2007)
Worldwide, millions of people are displaced annually because of natural or industrial disasters or social upheaval. Reliable data on the numbers, characteristics, and locations of these populations can bolster humanitarian relief efforts and recovery programs. Using sound methods for estimating population numbers and characteristics is important for both industrialized and developing nations. Ensuring that the data are geographically referenced for projection onto maps is essential. However, good data alone are insufficient. Adequate staff training and strong organizational and political desire to maintain and use the information are also required. Tools and Methods for Estimating Populations at Risk from Natural Disasters and Complex Humanitarian Crises, reviews the main methods and tools for making estimates of subnational populations and makes several recommendations to improve the collection and the use of population data for emergency response and development.
Keywords: Behavioral and Social Sciences; Earth Sciences; Conflict and Security Issues

Private-Public Sector Collaboration to Enhance Community Disaster Resilience: A Workshop Report - National Research Council (The National Academies Press, 2010)
The terrorist attacks of September 11, 2001 (9/11) on the United States prompted a rethinking of how the United States prepares for disasters. Federal policy documents written since 9/11 have stressed that the private and public sectors share equal responsibility for the security of the nation's critical infrastructure and key assets. Private sector entities have a role in the safety, security, and resilience of the communities in which they operate. Incentivizing the private sector to expend resources on community efforts remains challenging. Disasters in the United States since 9/11 (e.g., Hurricane Katrina in 2005) indicate that the nation has not yet been successful in making its communities resilient to disaster. In this book, the National Research Council assesses the current states of the art and practice in private-public sector collaboration dedicated to strengthening community disaster resilience.
Keywords: Policy for Science and Technology; Earth Sciences; Conflict and Security Issues

Building Community Disaster Resilience Through Private-Public Collaboration - National Research Council (The National Academies Press, 2011)
Natural disasters—including hurricanes, earthquakes, volcanic eruptions, and floods—caused more than 220,000 deaths worldwide in the first half of 2010 and wreaked havoc on homes, buildings, and the environment. To withstand and recover from natural and human-caused disasters, it is essential that citizens and communities work together to anticipate threats, limit their effects, and rapidly restore functionality after a crisis. Increasing evidence indicates that collaboration between the private and public sectors could improve the ability of a community to prepare for, respond to, and recover from disasters. Several previous National Research Council reports have identified specific examples of the private and public sectors working cooperatively to reduce the effects of a disaster by implementing building codes, retrofitting buildings, improving community education, or issuing extreme-weather warnings. State and federal governments have acknowledged the importance of collaboration between private and public organizations to develop planning for disaster preparedness and response. Despite growing ad hoc experience across the country, there is currently no comprehensive framework to guide private-public collaboration focused on disaster preparedness, response, and recovery. Building Community Disaster Resilience through Private-Public Collaboration assesses the current state of private-public sector collaboration dedicated to strengthening community resilience, identifies gaps in knowledge and practice, and recommends research that could be targeted for investment. Specifically, the book finds that local-level private-public collaboration is essential to the development of community resilience. Sustainable and effective resilience-focused private-public collaboration is dependent on several basic principles that increase communication among all sectors of the community, incorporate flexibility into collaborative networks, and encourage regular reassessment of collaborative missions, goals, and practices.
Keywords: Earth Sciences; Policy for Science and Technology; Conflict and Security Issues

Crisis Standards of Care: A Systems Framework for Catastrophic Disaster Response: Volume 1: Introduction and CSC Framework - Institute of Medicine (The National Academies Press, 2012)
Catastrophic disasters occurring in 2011 in the United States and worldwide—from the tornado in Joplin, Missouri, to the earthquake and tsunami in Japan, to the earthquake in New Zealand—have demonstrated that even prepared communities can be overwhelmed. In 2009, at the height of the influenza A (H1N1) pandemic, the Assistant Secretary for Preparedness and Response at the Department of Health and Human Services, along with the Department of Veterans Affairs and the National Highway Traffic Safety Administration, asked the Institute of Medicine (IOM) to convene a committee of experts to develop national guidance for use by state and local public health officials and health-sector agencies and institutions in establishing and implementing standards of care that should apply in disaster situations-both naturally occurring and man-made-under conditions of scarce resources. Building on the work of phase one (which is described in IOM's 2009 letter report, Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations), the committee developed detailed templates enumerating the functions and tasks of the key stakeholder groups involved in crisis standards of care (CSC) planning, implementation, and public engagement-state and local governments, emergency medical services (EMS), hospitals and acute care facilities, and out-of-hospital and alternate care systems. Crisis Standards of Care provides a framework for a systems approach to the development and implementation of CSC plans, and addresses the legal issues and the ethical, palliative care, and mental health issues that agencies and organizations at each level of a disaster response should address. Please note: this report is not intended to be a detailed guide to emergency preparedness or disaster response. What is described in this report is an extrapolation of existing incident management practices and principles. Crisis Standards of Care is a seven-volume set: Volume 1 provides an overview; Volume 2 pertains to state and local governments; Volume 3 pertains to emergency medical services; Volume 4 pertains to hospitals and acute care facilities; Volume 5 pertains to out-of-hospital care and alternate care systems; Volume 6 contains a public engagement toolkit; and Volume 7 contains appendixes with additional resources.
Keywords: Health and Medicine; Conflict and Security Issues

Disaster Resilience: A National Imperative (The National Academies Press, 2012)
No person or place is immune from disasters or disaster-related losses. Infectious disease outbreaks, acts of terrorism, social unrest, or financial disasters in addition to natural hazards can all lead to large-scale consequences for the nation and its communities. Communities and the nation thus face difficult fiscal, social, cultural, and environmental choices about the best ways to ensure basic security and quality of life against hazards, deliberate attacks, and disasters. Beyond the unquantifiable costs of injury and loss of life from disasters, statistics for 2011 alone indicate economic damages from natural disasters in the United States exceeded $55 billion, with 14 events costing more than a billion dollars in damages each. One way to reduce the impacts of disasters on the nation and its communities is to invest in enhancing resilience—the ability to prepare and plan for, absorb, recover from and more successfully adapt to adverse events. Disaster Resilience: A National Imperative addresses the broad issue of increasing the nation's resilience to disasters. This book defines "national resilience", describes the state of knowledge about resilience to hazards and disasters, and frames the main issues related to increasing resilience in the United States. It also provide goals, baseline conditions, or performance metrics for national resilience and outlines additional information, data, gaps, and/or obstacles that need to be addressed to increase the nation's resilience to disasters. Additionally, the book's authoring committee makes recommendations about the necessary approaches to elevate national resilience to disasters in the United States. Enhanced resilience allows better anticipation of disasters and better planning to reduce disaster losses-rather than waiting for an event to occur and paying for it afterward. Disaster Resilience confronts the topic of how to increase the nation's resilience to disasters through a vision of the characteristics of a resilient nation in the year 2030. Increasing disaster resilience is an imperative that requires the collective will of the nation and its communities. Although disasters will continue to occur, actions that move the nation from reactive approaches to disasters to a proactive stance where communities actively engage in enhancing resilience will reduce many of the broad societal and economic burdens that disasters can cause.
Keywords: Earth Sciences; Policy for Science and Technology; Conflict and Security Issues

A Guide to Regional Transportation Planning for Disasters, Emergencies, and Significant Events - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 777: A Guide to Regional Transportation Planning for Disasters, Emergencies, and Significant Events uses foundational planning principles, case studies, tips, and tools to explain implementation of transportation planning for possible multijurisdictional disasters, emergencies, and other major events. In addition to the guide, there is a contractor's final research report and a PowerPoint presentation describing the entire project.
Keywords: Transportation and Infrastructure

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.
Keywords: Health and Medicine; Conflict and Security Issues

Preparedness and Response to a Rural Mass Casualty Incident: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Problems contacting emergency services and delayed assistance are not unusual when incidents occur in rural areas, and the consequences can be devastating, particularly with mass casualty incidents. The IOM's Forum on Medical and Public Health Preparedness for Catastrophic Events held a workshop to examine the current capabilities of emergency response systems and the future opportunities to improve mass casualty response in rural communities.
Keywords: Health and Medicine

Facing Hazards and Disasters: Understanding Human Dimensions - National Research Council (The National Academies Press, 2006)
Social science research conducted since the late 1970's has contributed greatly to society's ability to mitigate and adapt to natural, technological, and willful disasters. However, as evidenced by Hurricane Katrina, the Indian Ocean tsunami, the September 11, 2001 terrorist attacks on the United States, and other recent events, hazards and disaster research and its application could be improved greatly. In particular, more studies should be pursued that compare how the characteristics of different types of events—including predictability, forewarning, magnitude, and duration of impact—affect societal vulnerability and response. This book includes more than thirty recommendations for the hazards and disaster community.
Keywords: Behavioral and Social Sciences; Earth Sciences; Conflict and Security Issues

Improving Disaster Management: The Role of IT in Mitigation, Preparedness, Response, and Recovery - National Research Council (The National Academies Press, 2007)
Information technology (IT) has the potential to play a critical role in managing natural and human-made disasters. Damage to communications infrastructure, along with other communications problems exacerbated the difficulties in carrying out response and recovery efforts following Hurricane Katrina. To assist government planning in this area, the Congress, in the E-government Act of 2002, directed the Federal Emergency Management Agency (FEMA) to request the NRC to conduct a study on the application of IT to disaster management. This report characterizes disaster management providing a framework for considering the range and nature of information and communication needs; presents a vision of the potential for IT to improve disaster management; provides an analysis of structural, organizational, and other non-technical barriers to the acquisition, adoption, and effective use of IT in disaster; and offers an outline of a research program aimed at strengthening IT-enabled capabilities for disaster management.
Keywords: Computers and Information Technology; Earth Sciences; Conflict and Security Issues

Facing the Unexpected: Disaster Preparedness and Response in the United States - Kathleen J. Tierney; Michael K. Lindell; Ronald W. Perry (The National Academies Press, 2001)
Facing the Unexpected presents the wealth of information derived from disasters around the world over the past 25 years. The authors explore how these findings can improve disaster programs, identify remaining research needs, and discuss disaster within the broader context of sustainable development. How do different people think about disaster? Are we more likely to panic or to respond with altruism? Why are 110 people killed in a Valujet crash considered disaster victims while the 50,000 killed annually in traffic accidents in the U.S. are not? At the crossroads of social, cultural, and economic factors, this book examines these and other compelling questions. The authors review the influences that shape the U.S. governmental system for disaster planning and response, the effectiveness of local emergency agencies, and the level of professionalism in the field. They also compare technological versus natural disaster and examine the impact of technology on disaster programs.
Keywords: Explore Science; Conflict and Security Issues

Disasters by Design: A Reassessment of Natural Hazards in the United States - Dennis Mileti (The National Academies Press, 1999)
Disasters by Design provides an alternative and sustainable way to view, study, and manage hazards in the United States that would result in disaster-resilient communities, higher environmental quality, inter- and intragenerational equity, economic sustainability, and improved quality of life. This volume provides an overview of what is known about natural hazards, disasters, recovery, and mitigation, how research findings have been translated into policies and programs; and a sustainable hazard mitigation research agenda. Also provided is an examination of past disaster losses and hazards management over the past 20 years, including factors—demographic, climate, social—that influence loss. This volume summarizes and sets the stage for the more detailed books in the series.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues

American Hazardscapes: The Regionalization of Hazards and Disasters - Susan L. Cutter (The National Academies Press, 2001)
Barrier islands. Flood plains. Earthquake faults. Sometimes the environment poses threats to our well being, yet many of us continue to choose to live in risky or dangerous places. And on top of the "knowns" are the other, more hidden hazards related to environmental contamination that pose equally serious threats to our health and well being. But where are these places and what types of hazards are found there? American Hazardscapes examines the risks associated with living and owning property in diverse regions across the United States, offering dual perspectives: that of the geographer and that of the social science hazards researcher. The book summarizes what we already know about regional patterns of hazard events and losses during the previous three decades and goes further to shed light on the nature of the events themselves and their impact on society. Written for the relocating citizen and the policy maker alike, American Hazardscapes presents a regional ecology of disaster-prone or disaster-resistant states. It also offers thoughts on what local, state, and federal managers need to do to meet the challenge of reducing hazard losses in the next century.
Keywords: Explore Science; Earth Sciences; Conflict and Security Issues